Insole optical fiber Bragg grating sensors network for dynamic vertical force monitoring - Domingues, M. F.; Tavares, C.; Leitão, C.; Frizera-Neto, A.; Alberto, N.; Marques, C.; Radwan, A.; Rodriguez, J.; Postolache, O.; Rocon, E.; André, P.; Antunes, P. (Journal of Biomedical Optics, 2017)
In an era of unprecedented progress in technology and increase in population age, continuous and close monitoring of elder citizens and patients is becoming more of a necessity than a luxury. Contributing toward this field and enhancing the life quality of elder citizens and patients with disabilities, this work presents the design and implementation of a noninvasive platform and insole fiber Bragg grating sensors network to monitor the vertical ground reaction forces distribution induced in the foot plantar surface during gait and body center of mass displacements. The acquired measurements are a reliable indication of the accuracy and consistency of the proposed solution in monitoring and mapping the vertical forces active on the foot plantar sole, with a sensitivity up to 11.06 pm/N. The acquired measurements can be used to infer the foot structure and health condition, in addition to anomalies related to spine function and other pathologies (e.g., related to diabetes); also its application in rehabilitation robotics field can dramatically reduce the computational burden of exoskeletons' control strategy. The proposed technology has the advantages of optical fiber sensing (robustness, noninvasiveness, accuracy, and electromagnetic insensitivity) to surpass all drawbacks verified in traditionally used sensing systems (fragility, instability, and inconsistent feedback).